(untitled) (American Journal of Technology and Applied Sciences, 2023)
In this paper, a fruit tree seedling planting machine is used in the establishment of new orchards to ensure continuous and mechanized planting of seedlings. It shows the costs used in planting seedlings and ways to reduce labor costs and increase productivity.